Shesto mezhdunarodno bienale na khumora i satirata v izkustvata - Ikanomov (1983)
Colourful jester's hat with a palette for a head, and a pencil intersecting through it Poster advertising international biennial on humour and satire in the arts, held in Gabrovo, Bulgaria, 28 May-30 September. Original title: Шесто международно биенале на хумора и сатирата в изкуствата PO-1509